Over a million students use our free study notes to help them with their homework
6.4 kg
The chain rule is used to find the derivative of an expression in the form h(f(x)) where you have a function in terms of a function of x for example:h(f(x)) = 2(3x+1)^3 where f(x) = 3x+1 In or...
Quadratic equations take the form ax^2 + bx + c = 0. In the case above, a = 0, b = -5, c = -14. In order to solve it, we can factorise the equation into the form (x+c)(x+d) = 0. The answers are then x = -...
steps as follows:x times x = x22 times 5 = 102 times x = 2xx times 5 = 5xthen add these together:y = x2 + 7x +10x = -2, -5; y = 0, 10
sin(2x)=sin(x+x) =sin(x)cos(x)+cos(x)sin(x) =2*sin(x)*cos(x); cos(2x)=cos(x+x) =cos(x)cos(x)-sin(x)sin(x) =[cos(x)]2-[sin(x)]2 Now let x+y=a and x-y=b, then x=(a+b)/2 and y=(a-b)/2. ...
←
513
514
515
516
517
→
Internet Safety
Payment Security
Cyber
Essentials